Improvement on the reception of weather satellite receiver at itm site by means of a bandpass filter, vhf amplifier and balun / Azdzidy Teh Azman Teh - Azman Teh, Azdzidy Teh (1997)
A VHF filter and amplifier is designed to improve the gain of the receiver antenna, in order to achieve its specifïcation. The amplifier was designed using the S-parameters with the aid of Smith chart to get the matching network of the amplifier. Impedance matching in antenna measurement is achieved by means of a balun to overcome the mismatch between the antenna and the signal generator. Key components of the system are a spectrum analyzer, signal generator, balun, bandpass filter and a VHF amplifier.